Volatiles and char combustion rates of demineralised lignite and wood blends - Yilgin, Melek; Pehlivan, Dursun (Elsevier Sci Ltd, 2009)
Today, much interest is given to the utilisation of materials of plant origin as substitutions of fossil fuels in meeting energy needs to reduce the level of atmospheric pollutant emissions and global warming threat, and emphasis has been placed on the co-combustion of coal and biomass. In this study, volatiles and char combustion behaviour of the fuel pellets composed from demineralised lignite and poplar wood sawdust, were investigated in a cylindrical wire mesh basket placed in a preheated tube furnace. The results have shown that ignition times of the pellets decreased with the burning temperature and shortened further due to demineralisation of lignite. Volatiles combustion rates of the samples did not correlate well with combustion times. However, they can be correlated with their respective proximate volatile matter contents. Char burnout times decreased with increasing combustion rates and correlated well with the respective proximate fixed carbon contents of the samples. Deviations were more considerable in the case of rate data. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Co-combustion; Lignite; Poplar wood; Volatiles combustion; Char combustion